2021
DOI: 10.1016/j.mjafi.2021.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of ChAdOx1 nCOV-19 Vaccine: Experience of a tertiary care institute

Abstract: Background The first dose of the ChAdOx1 nCoV- 19 Corona Virus Vaccine (Covishield) was administered to the eligible beneficiaries of tertiary care institute of Western Maharashtra on 16 Jan 21 and in the past three months almost 97% of the staff has been vaccinated. The present study analyses the incidence of COVID cases in the unvaccinated and vaccinated population of the institute. Methods All Covid 19 infections (RT-PCR positive) from 01 February 21 to 25 April 21 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Several studies have shown the efficacy of the ChAdOx1 nCoV-19 vaccine in the prevention of symptomatic and severe cases of COVID-19 in different populations including the elderly (significant vaccine efficacy of 70.4% after two doses) [ 69 , 70 , 71 ]. However, its efficacy, represented by neutralizing antibody activity, is much less when compared to mRNA vaccines [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the efficacy of the ChAdOx1 nCoV-19 vaccine in the prevention of symptomatic and severe cases of COVID-19 in different populations including the elderly (significant vaccine efficacy of 70.4% after two doses) [ 69 , 70 , 71 ]. However, its efficacy, represented by neutralizing antibody activity, is much less when compared to mRNA vaccines [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The slow roll out of vaccines in L/MICs may partially explain this disparity in evaluations, but this explanation seems incomplete, as vaccines have often been deployed in poor countries in a phased fashion, creating subpopulations for whom vaccine coverage would be high enough to evaluate effectiveness, as has been done in three studies in India. 13 , 17 , 24 Moreover, our review found no studies of the effectiveness of the 17 vaccines not yet approved by WHO, which to a large extent have been purchased by or allocated to poorer countries. Without effectiveness studies, the basis for using many of these vaccines may remain unclear.…”
Section: Evidence Gap In Effectiveness Evaluation In Lmicsmentioning
confidence: 93%
“…As shown in Table 1 , we identified 58 papers that included 85 evaluations of the effectiveness of different COVID-19 vaccines (some of the papers simultaneously evaluated more than one vaccine). 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 There were no published studies of vaccines that had not received WHO EUL at the time of the survey. Only three studies evaluated vaccines deployed in L/MICs (all three in India), and 79 (93%) of the evaluations were done in high income countries.…”
Section: Effectiveness Evaluation Of Covid-19 Vaccines: the Available Evidencementioning
confidence: 99%
“…Evidence from 15 studies from the previous review (Allen et al 2021, Braeye et al 2021, de Gier et al 2021b, Harris et al 2021a, Harris et al 2021b, Layan et al 2022, Meyer et al 2021, Prunas et al 2022, Allen et al 2022b, Bobdey et al 2021, Clifford et al 2021, Hsu et al 2021, Martinez-Baz et al 2021, Ng et al 2021 suggested that fully vaccinated index cases transmitted pre-Delta variant and Wild-type SARS-CoV-2 to their contacts less than unvaccinated index cases, and this reduction was substantial (e.g. >50% reduction in transmission) in many studies.…”
Section: Evidence For Pre-delta Variantsmentioning
confidence: 99%